FAKTOR-FAKTOR YANG MEMPENGARUHI PERNIKAHAN USIA MUDA (STUDI KASUS DI DUSUN IX SEROJA PASAR VII TEMBUNG KECAMATAN PERCUT SEI TUAN KABUPATEN DELI SERDANG) - Hotnatalia Naibaho (Welfare StatE, 2013)
Marriage is a very important event and never forgotten in the course of one's life in a form and build a happy family. Marriage at a young age is a lot happening in some circles both in cities and villages. As in Dusun IX Seroja Pasar VII Tembung Percut Sei Tuan Deli Serdang regency. The marriage at a young age is influenced by various factors that encourage them to establish a marriage at a young age . The study was conducted in Dusun IX Seroja Pasar VII Tembung Percut Sei Tuan Deli Serdang regency. This study is descriptive, where informants in this study is that couples who had been married at a young age as many as 6 people and a religious leader. Data collection techniques to the study of literature, field studies, in-depth interviews and observation. The data obtained in the field and then analyzed by researchers who described qualitatively, so that in the end it can be concluded from these findings . The results showed that the dominant factor in the young marriage in Dusun IX Seroja Pasar VII Tembung Percut Sei Tuan due to pregnancy out of wedlock ( Marrige By acident ) and not only that there are other factors that cause them to get married at a young age as factors willingness itself ( feel 've loved each other ), factor encouragement of parents / families, as well as the educational factor is so low due to the economic situation which is toomediocre. Key words : Economic factors, education, willingness itself , parents / families, mass media, pregnancy outside marriage, marriage young age